Transcription Factor Interplay between LEAFY and APETALA1/CAULIFLOWER during Floral Initiation. Issue 2 (6th April 2017) - Goslin, Kevin; Zheng, Beibei; Serrano-Mislata, Antonio; Rae, Liina; Ryan, Patrick T.; Kwaśniewska, Kamila; Thomson, Bennett; Ó'Maoiléidigh, Diarmuid S.; Madueño, Francisco; Wellmer, Frank; Graciet, Emmanuelle
Abstract : LEAFY and APETALA1/CAULIFLOWER have partially antagonistic activities in the control of floral initiation. Abstract: The transcription factors LEAFY (LFY) and APETALA1 (AP1), together with the AP1 paralog CAULIFLOWER (CAL), control the onset of flower development in a partially redundant manner. This redundancy is thought to be mediated, at least in part, through the regulation of a shared set of target genes. However, whether these genes are independently or cooperatively regulated by LFY and AP1/CAL is currently unknown. To better understand the regulatory relationship between LFY and AP1/CAL and to obtain deeper insights into the control of floral initiation, we monitored the activity of LFY in the absence of AP1/CAL function. We found that the regulation of several known LFY target genes is unaffected by AP1/CAL perturbation, while others appear to require AP1/CAL activity. Furthermore, we obtained evidence that LFY and AP1/CAL control the expression of some genes in an antagonistic manner. Notably, these include key regulators of floral initiation such as TERMINAL FLOWER1 ( TFL1 ), which had been previously reported to be directly repressed by both LFY and AP1. We show here that TFL1 expression is suppressed by AP1 but promoted by LFY. We further demonstrate that LFY has an inhibitory effect on flower formation in the absence of AP1/CAL activity. We propose that LFY and AP1/CAL act as part of an incoherent feed-forward loop, a network motif where two interconnected pathways or transcription factors act in opposite directions on a target gene, to control the establishment of a stable developmental program for the formation of flowers.